GANTI RUGI DAN REHABILITASI DALAM PERSPEKTIF KITAB UNDANG-UNDANG HUKUM ACARA PIDANA - Rays, M. Ikhwan (Jurnal Yustisiabel, 2025)
Indonesian Criminal Procedure Law upholds human rights compared to the Dutch East Indies legacy of HIR, which ignores it. One of the main rights accommodated in the Criminal Procedure Code is the principle of presumption of innocence, as well as other rights such as legal aid, legal counsel, and the right to compensation and rehabilitation. This study aims to analyze the causes of compensation in the Criminal Procedure Code and the procedures for rehabilitation for individuals who experience errors in the judicial process. This study uses a normative method with a literature study. The results of the study indicate that rehabilitation can be submitted through a pretrial motion (Article 97, paragraph (3) of the Criminal Procedure Code) for suspects/defendants who experience errors in the legal process. Meanwhile, for defendants who are acquitted or released, rehabilitation is given in the verdict (Article 97, paragraphs (1) and (2) of the Criminal Procedure Code) or based on SEMA No. 11 of 1985 if it is not included in the verdict